Proceedings of the 2017 ACM on Web Science Conference 2017
DOI: 10.1145/3091478.3091488
|View full text |Cite
|
Sign up to set email alerts
|

"(Weitergeleitet von Journalistin)"

Abstract: Previous research has shown the existence of gender biases in the depiction of professions and occupations in search engine results. Such an unbalanced presentation might just as likely occur on Wikipedia, one of the most popular knowledge resources on the Web, since the encyclopedia has already been found to exhibit such tendencies in past studies. Under this premise, our work assesses gender bias with respect to the content of German Wikipedia articles about professions and occupations along three dimensions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The content analysis of data pertaining to the gender gap on Wikipedia offers a comprehensive view of the research landscape in this area. Academic literature consistently highlights the bidirectional relationship between biased contribution and the gender gap in encyclopedic content (Zagovora;Flöck;Wagner, 2017;Cabrera et al, 2018). This reciprocal relationship underscores that bias in participation and content mutually reinforce each other.…”
Section: Discussionmentioning
confidence: 94%
“…The content analysis of data pertaining to the gender gap on Wikipedia offers a comprehensive view of the research landscape in this area. Academic literature consistently highlights the bidirectional relationship between biased contribution and the gender gap in encyclopedic content (Zagovora;Flöck;Wagner, 2017;Cabrera et al, 2018). This reciprocal relationship underscores that bias in participation and content mutually reinforce each other.…”
Section: Discussionmentioning
confidence: 94%
“…The study reveals that white individuals and those with citizenship in Europe and North America are over represented in comparison to the rest of the world. In similar lines, there exists research works [32], attributed to Wikipedia, a sister project of Wikidata in which authors tried to reveal how imbalanced the gender presentation is on the occupations pages of Wikipedia. Authors in [12] studied gender differences in various Wikipedia language (European) editions with respect to the coverage of the Members of the European Parliament (MEP).…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, visual asymmetry could be displayed in non-biographical content. For example, research on German Wikipedia found that images used to describe occupations have an evident gender asymmetry: almost half of the images from the profession articles show men, and only around 12% depict women (Zagovora et al, 2017).…”
Section: Content Buildingmentioning
confidence: 99%